High frequency of Machado-Joseph disease identified in Southeastern Chinese kindreds with spinocerebellar ataxia - Gan Shi-Rui; Shi Sheng-Sheng; Wu Jian-Jun; Wang Ning; Zhao Gui-Xian; Weng Sheng-Tong; Murong Shen-Xing; Lu Chuan-Zhen; Wu Zhi-Ying (BMC, 2010)
Abstract Background Machado-Joseph disease (MJD), caused by a CAG repeat expansion located in exon10 of the ATXN3 gene, is now regarded as one of the most common spinocerebellar ataxia (SCA) in the world. The relative frequency of MJD among SCA has previously been estimated at about 50% in the Chinese population and has been reported to be related to the frequency of large normal alleles in some populations. Taq polymerase has been used for PCR in nearly all studies reported previously. Methods Normal and expanded alleles of ATXN3 were detected via PCR using LA Taq DNA polymerase (better for GC-rich sequences) and denaturing polyacrylamide gel electrophoresis in 150 normal individuals and 138 unrelated probands from autosomal dominant SCA families. To compare reaction efficiency, 12 MJD patients' expanded alleles were amplified with La Taq and Taq polymerase respectively in the same amplifying systems and reaction conditions. Results Normal alleles ranged from 12 to 42 CAG repeats. The most common allele contained 14 repeats with a frequency of 23.3%, which corroborates previous reports. The frequency of large normal alleles (>27 repeats) was 0.28, which was very high relative to previous reports. The frequency of MJD in SCA patients was 72.5%, which was significantly higher than those in previous reports about the Chinese and other Asian populations. This frequency was one of the highest reported worldwide, with only Portuguese and Brazilian populations exhibiting higher proportions. All 12 expanded alleles were amplified in PCR with La Taq polymerase, whereas only 2 expanded alleles were amplified with Taq polymerase. Conclusion We have first reported the highest relative frequency of MJD in Asia, and we attribute this high frequency to a more efficient PCR using LA Taq polymerase and hypothesized that large ANs may act as a reservoir for expanded alleles in the Southeastern Chinese population.